Early High-Risk Opioid Prescribing Practices and Long-Term Disability Among Injured Workers in Washington State, 2002 to 2013 - Haight, John R. (J Occup Environ Med, 2020)
To estimate associations between early high-risk opioid prescribing practices and long-term work-related disability. METHODS: Washington State Fund injured workers with at least one opioid prescription filled within 6 weeks after injury (2002 to 2013) were included (N = 83,150). Associations between early high-risk opioid prescribing (longer duration, higher dosage, concurrent sedatives), and time lost from work, total permanent disability, and a surrogate measure for Social Security disability benefits were tested. Measures of early hospitalization, body part, and nature of injury were included to address confounding by indication concerns, along with sensitivity analyses controlling for injury severity. RESULTS: In adjusted logistic models, early high-risk opioid prescribing was associated with roughly three times the odds of each outcome. CONCLUSION: Exposure to high-risk opioid prescribing within 90 days of injury was significantly and substantially associated with long-term temporary and permanent disability.